Development of web-based interactive multimedia for human resource management learning in vocational high schools - Anis Susanti; Wiedy Murtini; Harini Harini (Jurnal Pendidikan Vokasi, 2018)
The purpose of this study is to find out the feasibility and the effectiveness of web-based interactive multimedia called EMMASY. This multimedia was developed for learning automation of the personnel administration in vocational high schools. The type of this research is a research and development using the design of learning multimedia development from Alessi and Trollip which includes planning, design, and development. At the development stage, alpha test was conducted by the experts of media and materials to determine the feasibility followed by beta test by the users to find out the usefulness and summative test to find out the effectiveness. In summative test, the sampling technique was purposive. The data of Interviews and observation were analysed descriptive-qualitatively while the data of questionnaire and tests were analysed descriptive-quantitatively. The results showed that EMMASY is very feasible as a learning multimedia with the media-expert's score of 93.12% and the material-expert's score of 93.75%. The result of the usability test showed a score of 79.6% with feasible category. The result of summative test using independent samples t-test showed t-test significance value of 0.008 less than 0.05. In addition, tobs > ttable (9.009 > 2.048) meaning that there is significant mean score difference of the students' knowledge in experimental and control classes; so EMMASY is considered effective to improve students' understanding of human-resource-management materials.